Emotional and behavioural problems in children and adolescents with primary headache - Just, Ulrike; Oelkers-Ax, Rieke; Bender, Stephan; Parzer, Peter; Ebinger, Friedrich; Weisbrod, Matthias; Resch, Franz (Cephalalgia, 2003)
Psychiatric co-morbidity is an important risk factor for chronification of primary headache into adulthood. The aim of this study was to investigate the extent and clinical relevance of emotional and behavioural problems in children and adolescents with primary headache. Children and adolescents (n = 128) with primary headache (International Headache Society, codes 1.1, 1.2, 2.1) and 83 matched controls aged 6-18 years were examined by standardized dimensional psychometrical tests (Child Behaviour Checklist, Depression Inventory for Children and Adolescents, Anxiety Questionnaire for Pupils). Children and adolescents with primary headache suffer more often from internalizing problems (depression, anxiety, somatization) than healthy controls. The detected emotional and behavioural problems are clinically relevant and require particular therapy in every third child suffering from headache. Two out of three children and adolescents with primary headache do not show clinically relevant psychopathology and may benefit from minimal therapeutic intervention. One of three examined headache patients needs additional psychiatric therapy.